International Baccalaureate Middle Years Program: an empirical study - Magee, Deidre Houston, author; Cobb, R. Brian, advisor; Cooner, Donna, advisor; Foster, Ann, committee member; Reid, Louann, committee member (Colorado State University. Libraries, 2005)
The International Baccalaureate Middle Years Program (IBMYP) provides a rigorous academic course of study for students. The IBMYP concentrates on the interrelatedness of language, math, science, geography, history and the arts. The IBMYP provides students with the prerequisite skills to enter the IB Diploma Program (IBO, 2003). This study of the International Baccalaureate Middle Years Program (IBMYP) at a high school located in the mountain west region of the United States was a quantitative, quasi-experimental, ex-post facto, posttest only research design. The study explored the relationship between an academic program of study (IBMYP) and student achievement. ACT Reading and Math scores were the dependent variable and the covariate was achievement levels test (ALT) scores. The purpose of this study was to determine if there was a difference in the ACT Math and ACT Reading scores of students who participated in IBMYP and matched peers who studied the traditional curriculum. The data set was requested and obtained from the school District Office of Student Achievement, Data and Assessment. The ANCOVA results showed that there was statistical significance for the main effect of IB participation and Non-IB participation for ACT Reading and ACT Math scores when controlling for prior achievement. There was no statistical significance in the interactions of IB/Non-IB with gender and ethnicity. The results of this study revealed patterns of higher ACT Reading and Math scores for IBMYP students when controlling for prior achievement levels. This study was framed within the context of the goals of schooling in the United States as articulated by the research of John I. Goodlad. The goals of schooling are to provide for the academic, vocational, social/civic and personal development of individual students while developing democratic character in the next generation. The findings of this study show that the components of the IB curriculum are reflective of recommended goals for schooling in the United States. The statistical data generated in this study will add to the limited information available on the IBMYP and student achievement.
Keywords: curricula; teaching; secondary education; curriculum development